EEG-Based Detection of Braking Intention Under Different Car Driving Conditions - Hernández, Luis G.; Mozos, Oscar Martinez; Ferrández, José M.; Antelis, Javier M. (Frontiers in Neuroinformatics, 2018)
The anticipatory recognition of braking is essential to prevent traffic accidents. For instance, driving assistance systems can be useful to properly respond to emergency braking situations. Moreover, the response time to emergency braking situations can be affected and even increased by different driver’s cognitive states caused by stress, fatigue, and extra workload. This work investigates the detection of emergency braking from driver’s electroencephalographic (EEG) signals that precede the brake pedal actuation. Bioelectrical signals were recorded while participants were driving in a car simulator while avoiding potential collisions by performing emergency braking. In addition, participants were subjected to stress, workload and fatigue. EEG signals were classified using support vector machines (SVM) and convolutional neural networks (CNN) in order to discriminate between braking intention and normal driving. Results showed significant recognition of emergency braking intention which was on average 71.1% for SVM and 71.8% CNN. In addition, the classification accuracy for the best participant was 80.1% and 88.1% for SVM and CNN, respectively. These results show the feasibility of incorporating recognizable driver’s bioelectrical responses into advanced driver-assistance systems to carry out early detection of emergency braking situations which could be useful to reduce car accidents.